Changes in fatty acid profile during larval development of freshwater prawn macrobrachium rosenbergii (de man) - Roustaian, P.; Kamarudin, M S.; Omar, H.; Saad, C R.; Ahmad, M H. (Wiley, 2001)
The fatty acid profile of Macrobrachium rosenbergii (de Man) larvae grown under hatchery conditions was studied during development from larval stage I to IX. The larvae were reared under a 'modified static green water' system with a modification in which the tanks were not seeded by green water at the beginning of culture period. Feeding with newly hatched Artemia nauplii started at stage II with five or six Artemia per larva, which was then gradually increased to 60 organisms per larva at stage IX when the study was terminated. In general, fatty acid composition changed during larval development, with the greatest variations observed from stage I to stage III. Monounsaturated fatty acids constituted the major moiety of fatty acids of stage I whereas polyunsaturated fatty acids were the dominant fatty acid class in later developmental stages. Moreover, polyunsaturated fatty acids were dominated by n-6 series in stage I and by n-3 series for the rest of the larval stages. The major fatty acids of the stage I larvae were palmitic (16:0), oleic/vaccenic (18:1) and linoleic (18:2n-6) acids, whereas for the rest of the larval stages, palmitic (16:0), stearic (18:0), oleic/vaccenic (18:1), linolenic (18:3n-3) and eicosapentaenoic (20:5n-3) acids were the prominent fatty acids. Although decreases in total saturated fatty acids and monounsaturated fatty acids were observed, polyunsaturated fatty acids tended to increase during larval development. Unlike penaeid larvae, M. rosenbergii larvae appeared to have sufficient capability to convert palmitic (16:0) acid to stearic (18:0) acid. Moreover, dietary linoleic (18:2n-6) and linolenic (18:3n-3) acids appeared to be converted to arachidonic (20:4n-6) and eicosapentaenoic (20:5n-3) acids to meet larval demand for such highly unsaturated fatty acids respectively.